Peran Asupan Zink dan Vitamin D terhadap Perkembangan Kognitif dan Fisik Anak - Rojwa Azka Syakira; Dian Isti Angraini; Muhammad Aditya; Reni Zuraida (Pusat Riset dan Inovasi Nasional, 2026)
Physical and cognitive development in children are strongly affected by adequate intake of zinc and vitamin D, as both nutrients play essential roles in bone formation, motor skills, immune function, and neurocognitive processes such as memory and learning. This review compiles evidence from studies published over the last decade showing that sufficient zinc intake is linked to improved linear growth, neuromuscular coordination, and overall motor performance. Meanwhile, vitamin D supports optimal absorption of calcium and phosphorus, promotes skeletal integrity, and may also contribute to cognitive development. Several studies emphasize the synergistic relationship between zinc and vitamin D, particularly through vitamin D receptor activity that involves zinc-finger domains, highlighting how deficiencies in both nutrients can increase the risk of impaired growth and cognitive delays in children. The findings underscore the importance of ensuring adequate nutritional intake through balanced diets, appropriate sunlight exposure, food fortification programs, and targeted supplementation for vulnerable populations. Addressing these nutritional needs is crucial for supporting optimal physical growth, brain development, and long-term health outcomes in children.